2017
DOI: 10.1186/s12906-017-1978-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-market outcome of an extract of traditional Cretan herbs on upper respiratory tract infections: a pragmatic, prospective observational study

Abstract: BackgroundThe beneficial effects of traditional herbs of Crete, Greece for the treatment of upper respiratory tract infections have been reported in observational and laboratory studies. Following a published, double blind, randomized, placebo controlled trial, this study aimed to assess the effectiveness of an extract of three Cretan herbs on the treatment of upper respiratory tract infections, upon its market release.MethodsAn observational study was conducted in Heraklion, Crete, Greece. Participants were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…These animal toxicity data greatly support our previous evidence of the absence of short-term toxicity for CAPeo from the double-blind randomized controlled clinical study, where participants received CAPeo for 7 days 9,10 . Analyzing the same hematological and biochemical parameters (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These animal toxicity data greatly support our previous evidence of the absence of short-term toxicity for CAPeo from the double-blind randomized controlled clinical study, where participants received CAPeo for 7 days 9,10 . Analyzing the same hematological and biochemical parameters (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…As a result, many therapeutic agents have been developed. Under this scope, CAPeo (Cretan Aromatic Plants essential oil) was formulated, taking advantage of previous observational studies of our group 5 , exhibiting significant antiviral properties and reducing the duration and severity of symptoms of upper respiratory tract infections 9 , 10 . However, since many plants can exert toxic effects, the assumption that a composition is safe because it is natural, needs careful consideration, as, in many cases, adverse reactions may occur if inappropriately used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this study, we have focused on three of the most efficient plants (Coridothymus capitatus, Salvia fruticosa and Origanum dictamnus) and developed a supplement, efficient at combatting upper respiratory tract infections (Duikler et al, 2015;Anastasaki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We systematically analyzed the habits of a rural population in Crete and reported that use of different plant infusions, alone or in combination, resulted in a significant protection from common cold and influenza infections ( Lionis et al, 1998 ). Based on this study, we have focused on three of the most efficient plants ( Coridothymus capitatus , Salvia fruticosa and Origanum dictamnus ) and developed a supplement, efficient at combatting upper respiratory tract infections ( Duikler et al, 2015 ; Anastasaki et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%